2020
DOI: 10.1016/j.jhin.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potential for pathogen dispersal during high-flow nasal therapy

Abstract: Keywords:High-flow nasal therapy Pathogen transmission Droplet infection S U M M A R YHigh-flow nasal therapy is increasingly used in hospitals because of its effectiveness and patient comfort. However, pathogens in the patient's nasal and oral cavities may be dispersed by forced air. This study aimed to investigate the risk of pathogen dispersal during high-flow nasal therapy. Liquid and bacterial dispersal were assessed via in-vitro experimental set-ups using a manikin. Thickened water or fresh yeast solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 10 publications
0
60
0
4
Order By: Relevance
“…During the 2003 SARS outbreak, there were reports of significant transmission secondary to non‐invasive ventilation . Manikin studies suggest that dispersal of liquid from high flow nasal oxygen at 60 L/min is minimal and significantly less than that caused by coughing and sneezing, providing that nasal cannulae are well fitted . Nevertheless, the risk to health care workers of aerosolisation remains unclear and will depend on many variables, including flow rates, ventilator pressures, patient coughing and cooperation, and the quality and fit of staff personal protective equipment (PPE).…”
Section: Non‐invasive Ventilation and High Flow Nasal Oxygen Therapymentioning
confidence: 99%
“…During the 2003 SARS outbreak, there were reports of significant transmission secondary to non‐invasive ventilation . Manikin studies suggest that dispersal of liquid from high flow nasal oxygen at 60 L/min is minimal and significantly less than that caused by coughing and sneezing, providing that nasal cannulae are well fitted . Nevertheless, the risk to health care workers of aerosolisation remains unclear and will depend on many variables, including flow rates, ventilator pressures, patient coughing and cooperation, and the quality and fit of staff personal protective equipment (PPE).…”
Section: Non‐invasive Ventilation and High Flow Nasal Oxygen Therapymentioning
confidence: 99%
“…As such, the ability to limit the overall environmental exposure becomes important. Although modeling of liquid and bacterial pathogen dispersal demonstrated that high flow therapy limited the dispersion to the area proximate to the face and cannula, the issue of partial contamination remains concerning 27. Particle sizes of droplets or aerosolized infectious pathogens can directly have bearing on transmission distance.…”
mentioning
confidence: 99%
“…There is no currently published evidence that HFNO is a risk factor for nosocomial transmission of respiratory pathogens 27‐30 . During the 2003 Toronto SARS‐CoV outbreak, HFNO was not found to be a risk factor for transmission to healthcare workers 29 .…”
Section: Intermediate Therapiesmentioning
confidence: 98%